The System for Assessment of the Effectiveness of Personnel Stimulation on the Basis of Integral Index - Yelisyeyeva, O. K.; Kutova, N. H. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The article’s objective is to construct the system for assessment ofpersonnel management performance and its testing on a sample of Ukrainian companies. Problems of personnel stimulation at company level are highlighted. It is proposed to build the mechanism for company personnel stimulation by functional approach. Indicators to be used for assessing the means of personnel stimulation (material stimulation, organizational stimulation, social and psychological stimulation) and personnel management modeling are given. The algorithm for estimating the integral index of the personnel stimulation effectiveness is recommended. Estimation of the index of social and psychological stimulation of company personnel by the proposed method is illustrated. By use of the proposed algorithm it is demonstrated that the material stimulation (salary rate) is the most important determinant of the highly effective personnel stimulation. The integral index of the personnel stimulation effectiveness is estimated by correlation and regression analysis for a sample of Ukrainian companies over 2011-2015. On its basis, the companies under study are grouped by level of personnel stimulation. Corrective measures to increase the integral index of the personnel stimulation effectiveness in each company under study are proposed. The matrix of corrective measures on personnel stimulation at these companies is constructed and used to find the range of estimates of the integral index of the personnel stimulation effectiveness. The quality of personnel stimulation mechanism at company level is assessed on the basis of the estimated integral index of the personnel stimulation effectiveness.